Seed Endophyte bacteria enhance drought stress tolerance in Hordeum vulgare by regulating, physiological characteristics, antioxidants and minerals uptake - Abideen, Zainul; Cardinale, Massimiliano; Zulfiqar, Faisal; Koyro, Hans-Werner; Rasool, Sarwat Ghulam; Hessini, Kamel; Darbali, Walid; Zhao, Fengliang; Siddique, Kadambot H.M. (Frontiers in Plant Science, 2022)
Growth stimulating bacteria help remediate dry arid soil and plant stress. Here, we used Pseudomonas sp. and Pantoea sp. to study the stress ecology of Hordeum vulgare and the environmental impact of water deficit on soil cherecterstics, growth, photosynthesis apparatus, mineral aquissition and antioxidiant defence. Both bacterial strains improved leaf growth and root development under well-watered conditions but reduced root biomass under drought stress. Plants inoculated with Pseudomonas or Pantoea had significantly higher soil carbon flux (soil respiration, which enhances soil microbial activity), chlorophyll content, net photosynthetic rate, and stomatal conductance than uninoculated plants in stressed conditions. Plants inoculated with Pseudomonas or Pantoea also increased leaf respiration and transpiration but decreased water use efficiency, photoinhibition, and the risk of oxidative stress (ETR/A). Drought stress increased K+ acquisition in both shoot and root of plants inoculated with Pseudomonas or Pantoea relative to non-stressed plants. Plants inoculated with Pseudomonas or Pantoea increased shoot Na+ while root Na+ only increased in plants inoculated with Pseudomonas in stressed conditions. Drought stress increased shoot Mg2+ in plants inoculated with Pseudomonas or Pantoea but did not affect Ca2+ relative to non-stressed plants. Drought stress only increased the K+/Na+ ratio in plants inoculated with Pseudomonas relative to non-stressed plants. Drought stress increased antioxidant enzymatic activities in plants inoculated with Pseudomonas or Pantoea, reducing membrane damage and improving oxidative defenses. Our results indicate that inoculating barley with the studied bacterial strains increased plant biomass and played a role in the environmental remediation of drylands for food production.